James! - Allcroft, Britt; Awdry, W. (Richmond, VIC : Hardie Grant Ergmont, 2017)
“Meet James! James is the number 5 red engine on the Island of Sodor. He has shiny red paint and a brass dome. James is a proud engine but lots of fun. This book is the perfect introduction for little fans of James!”--Back cover.
Title from cover.
"Fun facts! Favourtie sayings! Best friends!"--Cover.
"Thomas the Tank Engine & Friends created by Britt Allcroft. Based on the Railway series by the Reverend W. Awdry."--Back cover.
For children.
Keywords: James, -- the Red Engine (Fictitious character); Steam locomotives -- Juvenile fiction; Board books; Australian